2011
DOI: 10.1097/jto.0b013e3182307e1f
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytidine Deaminase and Xeroderma Pigmentosum Group D Polymorphisms with Response, Toxicity, and Survival in Cisplatin/Gemcitabine-Treated Advanced Non-small Cell Lung Cancer Patients

Abstract: Our data suggest polymorphic variations of drug metabolic gene were associated with response and toxicity of cisplatin/gemcitabine-based therapy and progression-free survival of patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 29 publications
4
38
1
1
Order By: Relevance
“…Severe GCB toxicity in NSCLC patients was reported in cases with heterozygous c.437CT variant and, to a lesser degree, in those with homozygous c.435TT variant (25,26). Interestingly, the latter was also found to be related to better response to GCB treatment, owing to reduced serum CDA concentration and higher exposure to active GCB metabolites (27,28).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Severe GCB toxicity in NSCLC patients was reported in cases with heterozygous c.437CT variant and, to a lesser degree, in those with homozygous c.435TT variant (25,26). Interestingly, the latter was also found to be related to better response to GCB treatment, owing to reduced serum CDA concentration and higher exposure to active GCB metabolites (27,28).…”
Section: Discussionmentioning
confidence: 93%
“…Data on the relationship between CDA polymorphisms and GCB toxicity are inconsistent (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Severe GCB toxicity in NSCLC patients was reported in cases with heterozygous c.437CT variant and, to a lesser degree, in those with homozygous c.435TT variant (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in practical terms, this translates to lower risk for treatment failures and for development of resistance to various anticancer agents in cancer cells with low repair capacity. it has already been shown for different types of tumours (hematological as well as solid) that carriership of allelic forms of DnA polymorphisms associated with lower capacity for DNA repair (specifically XPD polymorphisms in exon 10 and exon 23, as well as polymorphisms in several genes participating in repair by BeR and recombination) may predict higher rates of response to treatment and better outcomes in terms of progression-free survival (37,40,56). interestingly, there are exceptions to this, as it has been shown that the presence of the Gln allele of the lys751Gln polymorphism of the XPD gene may actually be associated with reduced survival in patients treated with combined platinum/5-fluorouracil regimens for advanced colorectal cancer (52).…”
Section: Using Information About Individual Repair Capacity For Desigmentioning
confidence: 99%
“…carriership of polymorphisms in the XPD, ERCC1 and XRCC1 genes conferring lower capacity for DnA repair has been shown to be associated with higher risk for acute and late toxicity in 'standard' chemotherapy or radiotherapy regimens (40,59). What is more, polymorphic variants of genes which are not known to be associated with substantial decrease in the capacity for DnA repair may apparently also modify the risk for toxicity following anticancer therapy, as the R allele of the P72R polymorphism has been found to be more frequent in vascular skin lesions following radiotherapy for breast cancer than the P allele (61).…”
Section: Using Information About Individual Repair Capacity For Desigmentioning
confidence: 99%